Agronomic characteristics of new mid-cycle peanut lines in the Triângulo Mineiro - Aparecido Filho, Antonio Carlos (2022)
The objective of this work was to evaluate the agronomic characteristics of mid-cycle peanut genotypes in Triângulo Mineiro. The experiment was installed in an area of ​​sugarcane renewal, in the 2021/22 harvest, located in the municipality of Campina Verde – MG. The experimental design used was in randomized blocks, with four replications. The treatments were seven strains (1253 OL, 2010 OL, 2091 OL, 2259 OL, 2471 OL, 2110 OL and 1944 OL), developed by Embrapa's Peanut Improvement Program (PMA). The plots consisted of two lines of three meters in length, with an interval of three meters between plots and spacing between lines of ninety centimeters. After harvest at 125 days after planting (DAP), the weight of 100 grains and productivity were evaluated. It is concluded that the highest masses of 100 grains were obtained with 1253 OL and 2010 OL, while these same genotypes obtained the highest yields, together with 2091 OL, for the edaphoclimatic conditions of the Triângulo Mineiro. Emphasizing that studies with genetic improvement should continue in order to select genotypes that are increasingly productive and that meet the characteristics of the country's growing regions.